Retinal detachment with multiple macrocysts in Stickler syndrome: case report and review of the literature - Liu, Guina; Hu, Ming; Cai, Chengcheng; Jiang, Xiaoshuang; Lu, Fang (Frontiers in Medicine, 2024)
Background Stickler syndrome is a hereditary connective tissue disorder associated with ocular, orofacial, musculoskeletal, and auditory impairments. Its main clinical characteristics include retinal detachment, hearing loss, and midface underdevelopment. In clinical practice, macrocyst is rarely reported in retinal detachment cases with Stickler syndrome. Case presentation We report the case of a 7-year-old child who developed a rhegmatogenous retinal detachment (RRD) in the right eye, accompanied by multiple peripheral macrocysts. The detachment was successfully surgically repaired with vitrectomy, retinal laser photocoagulation, cryotherapy and silicone oil tamponade. During the operation, a mini-retinectomy in the outer layer of each macrocyst was made for vesicular drainage and retinal reattachment. Genetic testing identified a pathogenic point mutation variant (c.1693C>T; p.Arg565Cys) in exon 26 of the COL2A1 gene. Six-months after the operation, the retina remained attached with improvement of best corrected visual acuity to 20/200. Conclusion Patients with Stickler syndrome may develop RRD of different severity. Macrocyst is rarely reported in previous literature of Stickler syndrome. In this case report, we share our experience in treating with multiple macrocysts in RRD and emphasize the importance of periodic follow-up for patients with Stickler syndrome.